MAP1203 Promotes Mycobacterium avium Subspecies paratuberculosis Binding and Invasion to Bovine Epithelial Cells - Everman, Jamie; Danelishvili, Lia; Flores, Lucero G.; Bermudez, Luiz (Frontiers in Cellular and Infection Microbiology, 2018)
Mycobacterium avium subspecies paratuberculosis (MAP) is the causative agent of Johne's disease, chronic and ultimately fatal enteritis that affects ruminant populations worldwide. One mode of MAP transmission is oral when young animals ingest bacteria from the collostrum and milk of infected dams. The exposure to raw milk has a dramatic impact on MAP, resulting in a more invasive and virulent phenotype. The MAP1203 gene is upregulated over 28-fold after exposure of the bacterium to milk. In this study, the role of MAP1203 in binding and invasion of the bovine epithelial cells was investigated. By over-expressing the native MAP1203 gene and two clones of deletion mutant in the signal sequence and of missense mutations changing the integrin domain from RGD into RDE, we demonstrate that MAP1203 plays a role in increasing binding in more than 50% and invasion in 35% of bovine MDBK epithelial cells during early phase of infection. Furthermore, results obtained suggest that MAP1203 is a surface-exposed protein in MAP and the signal sequence is required for processing and expression of functional protein on the surface of the bacterium. Using the protein pull-down assay and far-Western blot, we also demonstrate that MAP1203 interacts with the host dihydropyrimidinase-related protein 2 and glyceraldehyde 3-phosphate dehydrogenase proteins, located on the membrane of epithelial cell and involved in the remodeling of the cytoskeleton. Our data suggests that MAP1203 plays a significant role in the initiation of MAP infection of the bovine epithelium.